Habitat quality and surrounding landscape structures influence wild bee occurrence in perennial wildflower strips - Schubert, Lea F.; Hellwig, Niels; Kirmer, Anita; Schmid-Egger, Christian; Schmidt, Annika; Dieker, Petra; Tischew, Sabine (Basic and applied ecology, 2022)
Perennial wildflower strips (WFS) are known to have positive effects on wild bees in intensively used agricultural landscapes. Little knowledge exists, however, about the drivers of wild bee occurrence and if Red List species also profit from this agri-environmental scheme (AES). Therefore, we studied wild bees on transects along 20 four- to five-year-old WFS and in 10 cereal fields without AES (CONTROL sites) in differently structured landscapes across Saxony-Anhalt (Germany). In addition to local site parameters, we measured parameters of landscape structure in a 1 km radius of the WFS and CONTROL sites. The overall species richness of wild bees (125 species in total, 23 on average), including numerous specialist and Red List species, indicates a high attractiveness of perennial WFS sown with 30 native forbs. In CONTROL fields, 11 bee species (on average only one) were found. The species richness and abundance of wild bees were positively affected by local site conditions of the WFS and CONTROL sites, such as the overall number of sown and spontaneous forbs, the amount of flower rewards of sown forbs available to pollinators (Pollinator Feeding Index), and negatively by the cover of grasses. Therefore, seed mixtures of future AES should comprise a high diversity of wildflower species relevant as pollen sources for wild bees. The share of Red List wild bee species was strongly influenced by the landscape context and increased e.g. with Shannon landscape diversity and the availability of non-forest woody habitats and water bodies in the 1 km surroundings. These results suggest that besides the establishment of high-diversity WFS, semi-natural habitat structures have to be promoted to preserve rare wild bees especially in structurally simple agricultural landscapes. [Display omitted] •Wildflower mixtures with 30 native forbs attracted numerous common and rare wild bees.•Species richness and abundance of wild bees were mostly affected by WFS habitat quality.•Occurrence of red list wild bee species in WFS was influenced by landscape context.•WFS with high-diversity mixtures and semi-natural habitats should be promoted.